Penerapan Peraturan Daerah Nomor 5 Tahun 2017 Di Desa Mlancu Kecamatan Kandangan Kabupaten Kediri - MUSLIMIN; WAHYU PRASETIYO (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
Regional autonomy policy is a form of implementation of the principle of decentralization given by the central government to regional governments, in implementing national development carried out in accordance with local needs and characteristics. Regional autonomy gives authority to regional governments to regulate and manage the needs of the region itself, through the concept of development, directed at the development of the lowest level in the government structure, namely the village. Village officials are part of the government organizers in the village and have the task of assisting the village head in carrying out the duties and authorities of the village head. This study aims to: (1) describe the process of appointing village officials based on Regional Regulation Number 5 of 2017 concerning the Appointment and Dismissal of Mlancu Village Officials, Kandangan District, Kediri Regency. (2) to describe the process of dismissing village officials based on Regional Regulation Number 5 of 2017 concerning the Appointment and Dismissal of Mlancu Village Officials, Kandangan District, Kediri Regency. This study uses a qualitative research method with a descriptive approach. Data collection techniques in this study are interviews, observations, and documentation. Data analysis techniques in this study are data collection techniques, data reduction, data presentation, and drawing conclusions. The results of this study are: (1) the mechanism for appointing village officials is carried out in three stages, namely registration or recruitment, selection or screening exams and inauguration or appointment of village officials. (2) Dismissal of village officials is the authority of the village head. The head has the right to dismiss village officials with several factors. Factors that village officials can be dismissed if their term of office has expired, namely the age limit of 60 years, the village official resigns, the village official commits a violation that results in the village official becoming a convict or defendant and finally the village official stops if he dies during his term of office. For village officials who commit violations during their term of office, the village official will be dismissed directly and dishonorably by the village head.